COMMUNITY PARTICIPATION IN DEVELOPMENT IN NAGA VILLAGE, IBU TENGGAH, WEST HALMAHERA DISTRICT - GUHUHUKU, YOFIFI; RURU, JOORIE; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2019)
The purpose of the research is to explain the level of community participation in the development of Nagavillage, Ibu Tenggah, West Halmahera Regency. The study uses qualitative approach methods. Theinformant is one person as the head of the village, two people as a village officer/device, two as the head ofthe ward, and five people as the whole society as many as ten Informans. Based on the results of the studyshowed (1) community participation in decision making related to the development of Naga village, IbuTenggah, West Halmahera Regency may still be lacking, some people prefer to give authority Decisionmaking is done by the village apparatus although basically the village head and its ranks to take decisionsrelated to the development of the village adapted to the wishes of the village community related to thedevelopment of the village itself however. (2) Community participation in the construction of Naga village,Ibu Tenggah, West Halmahera Regency has been very good, where both people and village governmentswant to cooperate and mutual cooperation in the implementation of Village development Especially in thedevelopment and provision of facilities and infrastructure as well as village Infrastructuretus. In theimplementation of government programs also people always participate in it as evidence of theirparticipation both physically and nonphysically. (3) Community participation in the development results ofNaga Village, Ibu Tenggah, West Halmahera Regency has been very good. The awareness and sense ofresponsibility instilled by the village government to the community is extraordinary so that people are ableto utilize the results very well to be managed to become potential that can increase the resources People andnatural resources around them. People here care deeply and keep the results of their hard work and mutualassistance in development. Each development program and outcome is allocated evenly. (4) Communityparticipation in the evaluation related to the development of Naga village, Ibu Tenggah, West HalmaheraRegency has been quite good from the village government to have a meeting every month and each yearwith the community to listen to the input and of community-related developments.Keywords: Community Participation, Developmen,Village